Answer:
<u><em>y=7 </em></u><u>number of hours at grocery store</u>
<u><em>x=18 </em></u><u>number of hours at baby- sitting</u>
Step-by-step explanation:
According to the information provided.
x is number of hours at baby- sitting
y is number of hours at grocery store
total number of hours worked
<em>1) </em><em>x+y =25</em>
total earn in a week
<em>2) </em><em>x*$6 + y* $9 = $171</em>
<em />
<em>from equation 1</em>
x+y=25
x= 25-y
<em>we place the above derived equation in equation 2 </em>
x*$6 + y* $9 = $171
(25-y)*$6 + y* $9 = $171
(25*6) -6y +9y =171
150+3y=171
3y=171-150
3y=21
<u><em>y=7 </em></u><u>number of hours at grocery store</u>
x= 25-y
x= 25-7
<u><em>x=18 </em></u><u>number of hours at baby- sitting</u>
Answer:
Step-by-step explanation:
if y is hypotonuse and x is opposite side:
sin 34=x/8
8*sin 34=x
x=4.47 (3 sf)
tell me in comment if i interpreted question wrong ._.
105,000 would be the correct answer to your problem.
Answer:
270 cm^2
Step-by-step explanation:
This is quite easy.
There is formula for it, the formula is bh/2
b= is the base or side that the triangle's altitude or height is perpendicular to.
h= is the height of the triangle or the altitude of the triangle.
I can always like to thing that a triangle is like half of a rectangle because the area for a rectangle is bh, but in a triangle it is half the bh.
b= 30
h=18
Now substitute the values in the formula
30(18)/2
30 times 18 = 540
divide the product by 2
540/2 = 270
Hey there!
When finding the difference of expressions like these, there's a few things you should keep in mind.
1. When finding the difference of two polynomials, multiply the polynomial that implied to be "negative" by –1 to expand the problem and make it easier to solve.
2. You combine terms based on their unknown terms, like x, y, x², ab, etc. You cannot combine the terms x and x², but you can combine the terms 6b and 8b by adding them.
3. You can rearrange your terms however you see fit. If a polynomial is implied as "positive", you can multiply that entire polynomial by +1 to get rid of the parentheses.
With all that in mind, you can go ahead and solve for your difference, like so:
![(ab+8a+1)-(-6ab+4)](https://tex.z-dn.net/?f=%28ab%2B8a%2B1%29-%28-6ab%2B4%29)
![(ab+8a+1) (-1(-6ab+4))](https://tex.z-dn.net/?f=%28ab%2B8a%2B1%29%20%28-1%28-6ab%2B4%29%29)
![(ab+8a+1) + (6ab-4)](https://tex.z-dn.net/?f=%28ab%2B8a%2B1%29%20%2B%20%286ab-4%29)
![ab+6ab+8a+1-4](https://tex.z-dn.net/?f=ab%2B6ab%2B8a%2B1-4)
![7ab+8a-3](https://tex.z-dn.net/?f=7ab%2B8a-3)
![7ab+8a-3](https://tex.z-dn.net/?f=7ab%2B8a-3)
will be your difference.
Hope this helped you out! :-)